Unlocking Last-Mile Agent Networks for Effective and Responsible Scaling of Climate Smart Solutions - Ewell, Hanna Louise Deborah; Ouedraogo, Mathieu; Girvetz, Evan Hartunian (2025)
This infonote positions last-mile agent networks comprising agro-dealers, village-based advisors, and agripreneurs as critical social infrastructure for bridging the gap between agricultural research and on-farm adoption. These networks are pivotal for translating complex climate-smart innovations into trusted, locally relevant services, thereby ensuring that the benefits of innovation reach underserved groups, including women, youth, and remote communities. The infonote demonstrates that well-designed, commercially oriented agent networks are catalysts for systemic change. By bundling inputs, finance, advisory services, and market linkages through commission-based models, they unlock latent demand, reduce transaction costs, attract private and blended investment, and create sustainable pathways for scaling beyond project-dependent timelines.